Understanding the Differences Between Oncology Patients and Oncology Health Professionals Concerning Spirituality/Religiosity: A Cross-Sectional Study. Issue 47 (November 2015) - Camargos, Mayara Goulart de; Paiva, Carlos Eduardo; Barroso, Eliane Marçon; Carneseca, Estela Cristina; Paiva, Bianca Sakamoto Ribeiro
Abstract : Abstract: This study investigated whether spirituality/religiosity (S/R) plays an important role in the lives of cancer patients and in the work of health professionals who provide care for these patients. The correlations between spiritual quality of life (QOL) and the other QOL domain scores of patients and health professionals were also assessed. Moreover, QOL domain scores were compared between patients and health professionals. In this cross-sectional study, 1050 participants (525 oncology patients and 525 health professionals) were interviewed. Quality of life was assessed with the World Health Organization quality of life spiritual, religious, and personal beliefs (WHOQOL-SRPB). To compare the groups with respect to the instruments' domains, a quantile regression and an analysis of covariance model were used. The WHOQOL-Bref and WHOQOL-SRPB domains were correlated by performing Pearson and partial correlation tests. It was demonstrated that 94.1% of patients considered it important that health professionals addressed their spiritual beliefs, and 99.2% of patients relied on S/R to face cancer. Approximately, 99.6% of the patients reported that S/R support is necessary during cancer treatment; 98.3% of health professionals agreed that spiritual and religious support was necessary for oncology patients. Positive correlations between spiritual QOL and the other QOL domains were observed. When compared among themselves, patients exhibited significantly higher levels of spiritual QOL. In conclusion, S/R was an important construct in the minds of cancer patients and health professionals. Both groups often use S/R resources in their daily lives, which seems to positively affect their perceptions of QOL. Further studies are needed to determine how health professionals effectively address S/R during oncology practice.